The Impact of Career Development on Employee Job Satisfaction at PT Finex Bisnis Solution Futures in the Finance Division - Syahiddin, Muhamad Rafi (Jurnal Pengabdian Nusantara, 2025)
This study aims to analyze the effect of career development on employee job satisfaction at PT Finex Bisnis Solution Futures, focusing on the Finance Division. The research employs a literature-based qualitative approach by reviewing relevant theories, empirical findings, and case studies related to human resource management, career growth, and employee motivation. The study emphasizes that career development, which includes structured training programs, mentoring, fair promotion systems, and career counseling, significantly enhances job satisfaction and organizational commitment. Employees who perceive their organizations as supportive and fair in career advancement tend to show greater engagement, loyalty, and motivation. Furthermore, organizational support, leadership involvement, and transparent communication act as mediating factors that strengthen the relationship between career development and satisfaction. The findings underscore that career development should be viewed not only as a reward mechanism but also as a strategic investment in long-term human capital sustainability. In the context of financial service companies like PT Finex Bisnis Solution Futures, career development contributes to operational efficiency, retention, and overall performance. The implications of this study highlight the necessity for organizations to implement equitable and continuous development programs aligned with employees’ aspirations and the company’s strategic objectives.